Relationship between transcranial magnetic stimulation markers of motor control and clinical recovery in obsessive compulsive disorder/Gilles de la Tourette syndrome: a proof of concept case study - Quoilin, Caroline; Chaise, Fostine; Duque, Julie; de Timary, Philippe (Frontiers in Psychiatry, 2024)
Obsessive compulsive disorder (OCD) and Gilles de la Tourette Syndrome (GTS) are neurodevelopmental disorders characterized by difficulties in controlling intrusive thoughts (obsessions) and undesired actions (tics), respectively. Both conditions have been associated with abnormal inhibition but a tangible deficit of inhibitory control abilities is controversial in GTS. Here, we examined a 25-year-old male patient with severe OCD symptoms and a mild form of GTS, where impairments in motor control were central. Transcranial magnetic stimulation (TMS) was applied over the primary motor cortex (M1) to elicit motor-evoked potentials (MEPs) during four experimental sessions, allowing us to assess the excitability of motor intracortical circuitry at rest as well as the degree of MEP suppression during action preparation, a phenomenon thought to regulate movement initiation. When tested for the first time, the patient presented a decent level of MEP suppression during action preparation, but he exhibited a lack of intracortical inhibition at rest, as evidenced by reduced short-interval intracortical inhibition (SICI) and long-interval intracortical inhibition (LICI). Interestingly, the patient's symptomatology drastically improved over the course of the sessions (reduced obsessions and tics), coinciding with feedback given on his good motor control abilities. These changes were reflected in the TMS measurements, with a significant strengthening of intracortical inhibition (SICI and LICI more pronounced than previously) and a more selective tuning of MEPs during action preparation; MEPs became even more suppressed, or selectively facilitated depending on the behavioral condition in which they we probed. This study highlights the importance of better understanding motor inhibitory mechanisms in neurodevelopmental disorders and suggests a biofeedback approach as a potential novel treatment.